Quinazolinones as Competitive Inhibitors of Carbonic Anhydrase-II (Human and Bovine): Synthesis, in-vitro, in-silico, Selectivity, and Kinetics Studies - Khan, Ajmal; Khan, Majid; Halim, Sobia Ahsan; Khan, Zulfiqar Ali; Shafiq, Zahid; Al-Harrasi, Ahmed (Frontiers in Chemistry, 2020)
Carbonic anhydrase-II (CA-II) is associated with glaucoma, malignant brain tumors, renal, gastric and pancreatic carcinomas and mainly involved in the regulation of the bicarbonate concentration in the eyes. CA-II inhibitors can be used to reduce the intraocular pressure usually associated with glaucoma. In search of potent CA-II inhibitors, a series of quinazolinones derivatives (4a-p) were synthesized and characterized by IR and NMR spectroscopy. The inhibitory potential of all the compounds was evaluated against bovine carbonic anhydrase-II (bCA-II) and human carbonic anhydrase-II (hCA-II) and compounds displayed moderate to significant inhibition with IC50 values of 8.9 –67.3 and 14.0 – 59.6 µM, respectively. A preliminary structure-activity relationship suggested that the presence of nitro group on the phenyl ring at R position has remarkable contribution in the overall activity. Kinetics studies of the most active inhibitor 4d against both bCA-II and hCA-II were performed, to investigate the mode of inhibition and to determine the inhibition constants (Ki). According to the kinetics results, 4d is a competitive inhibitor of bCA-II and hCA-II with Ki values of 13.0 ± 0.013 and 14.25 ± 0.017 µM, respectively. However, the selectivity index reflects that the compounds 4g and 4o are more selective for hCA-II. The binding mode of these compounds within the active sites of bCA-II and hCA-II was investigated by structure-based molecular docking. The docking results are in complete agreement with the experimental findings.